Evaluasi Program Kegiatan P5-PPRA dengan Model CIPP di MTsN 2 Kediri - Azizah, Vani Nur; Hidayah, Noer; Hamidah, Ani Mar’atul (Edudeena : Journal of Islamic Religious Education, 2024)
Abstract: This research is motivated by the Independent Curriculum regulations which contain the P5-PPRA program. This program aims to shape the character and competence of students. This type of research uses qualitative research. Data was obtained through observation, interviews and documentation with data sources from teachers, students and related stakeholders. The data analysis technique uses the CIPP evaluation technique. The research results stated that the evaluation of the P5PPRA Activity Program with the CIPP Model at MTsN 2 Kediri was carried out on the Voice of Democracy Phase D theme. The form of evaluation was: 1) Evaluation of the visible context in the form of the background to which the program was held. The thing behind the implementation of the P5PPRA program is the determination of educational institutions to realize the character formation of students in practicing the Fourth Principle of Pancasila; 2) Evaluation of input which appears in the form of the role of institutions in supporting these activities is by bringing in resource persons from external institutions, namely from the KPU institution and providing election outreach activities; 3) Process Evaluation in this program, namely the implementation carried out based on established procedures, and 4) Product Evaluation in this program, namely the impact felt by students, namely increasing students' insight regarding the implementation of the Election. Abstrak: Penelitian ini dilatar belakangi oleh regulasi Kurikulum Merdeka yang memuat program P5-PPRA. Program ini memiliki tujuan membentuk karakter dan kompetensi peserta didik. Jenis penelitian menggunakan penelitian kualitatif. Data diperoleh melalui observasi, wawancara dan dokumentasi dengan sumber data dari guru, siswa, dan stakeholder yang berkaitan. Teknik analisa data menggunakan teknik evaluasi CIPP. Hasil penelitian menyebutkan bahwa Evaluasi Program Kegiatan P5PPRA dengan Model CIPP di MTsN 2 Kediri dilakukan pada tema Suara Demokrasi Fase D. Bentuk evaluasi berupa: 1) Evaluasi Konteks yang nampak berupa latar belakang diadakannya program tersebut. Hal yang melatarbelakangi pelaksanaan program P5PPRA adalah tekad lembaga pendidikan untuk mewujudkan pembentukan karakter peserta didik dalam mengamalkan Pancasila Sila Keempat; 2) Evaluasi Input yang nampak berupa peran lembaga dalam menunjang kegiatan tersebut adalah dengan mendatangkan narasumber dari lembaga luar, yakni dari lembaga KPU dan pengadaan kegiatan sosialisasi Pemilu; 3) Evaluasi Proses pada program ini yaitu pelaksanaan yang dilakukan berpedoman pada prosedur yang telah ditetapkan, dan 4) Evaluasi Produk pada program ini yaitu adanya dampak yang dirasakan oleh peserta didik yaitu menambah wawasan peserta didik terkait dengan pelaksanaan Pemilu.